PENGEMBANGAN VIDEO MOTION GRAPHICSSENI TARI JAIPONG KREASI - Rifki Risandhy; Achmad Syarief; Elda Franzia Jasjfi (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2019)
AbstractThe development of traditional dance 'Jaipong Kreasi' as one of the performing arts is still pretty good in the public. Any kinds of event in many regions still often stage it, but the development of Jaipong Kreasi dance in digital media is still slow due to little appreciation. Therefore, a development of motion graphic video is required for the traditional dance Jaipong Kreasi in order to provide an interesting spectacle for the public and as one of efforts to maintain the existence of local culture, in this case, Jaipong Kreasi dance art. Research is conducted by using qualitative approach with data collection technique through interview and observation. Subsequently, the data is analyzed under several phases, namely data reduction, data presentation, and conclusion. Motion graphics videos are designed with a modern and dynamic concept. giving the appearance of traditional dance to be fresher and up-to-date, but remain to consider the principles of Indonesian culture. AbstrakPerkembangan tari tradisional Jaipong Kreasi sebagai salah satu seni pertunjukkan masih cukup baik di masyarakat, namun pada media digital perkembangan taxi Jaipong Kreasi masih kurang mendapat apresiasi. Maka dari itu dibutuhkan suatu pengembangan video motion graphics pada taxi tradisional Jaipong Kreasi. Untuk memberikan sebuah tontonan yang menarik bagi masyarakat sebagai salah satu upaya dalam menjaga eksistensi budaya lokal seni tari Jaipong Kreasi. Penelitian dilakukan dengan menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara dan observasi. Berdasarkan hasil tersebut video motion graphics kemudian dirancang dengan konsep modern dan dinamis. Sehingga tampilan taxi tradisional menjadi lebih fresh dan kekinian, namun tetap memperhatikan kaidah-kaidah budaya Indonesia.